Galleria mellonella: An Infection Model for Screening Compounds Against the Mycobacterium tuberculosis Complex - Asai, Masanori; Li, Yanwen; Khara, Jasmeet Singh; Robertson, Brian D.; Langford, Paul R.; Newton, Sandra M. (Frontiers in Microbiology, 2019)
Drug screening models have a vital role in the development of novel antimycobacterial agents which are urgently needed to tackle drug-resistant tuberculosis (TB). We recently established the larvae of the insect Galleria mellonella (greater wax moth) as a novel infection model for the Mycobacterium tuberculosis complex. Here we demonstrate its use as a rapid and reproducible screen to evaluate antimycobacterial drug efficacy using larvae infected with bioluminescent Mycobacterium bovis BCG lux. Treatment improved larval survival outcome and, with the exception of pyrazinamide, was associated with a significant reduction in in vivo mycobacterial bioluminescence over a 96 hour period compared to the untreated controls. Isoniazid and rifampicin displayed the greatest in vivo efficacy and survival outcome. Thus G. mellonella, infected with bioluminescent mycobacteria, can rapidly determine in vivo drug efficacy, and has the potential to significantly reduce and/or replace the number of animals used in TB research.